2018
DOI: 10.1016/j.addbeh.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of future consequences as a moderator of the willingness-behavior relationship for young adult marijuana use and consequences

Abstract: The Prototype Willingness Model is a dual-processing (i.e., intentional and socially reactive) health-risk behavior model. The socially reactive path includes behavioral willingness, descriptive normative perceptions, and favorable images of individuals who engage in health-risk behavior (prototype favorability) as important predictors of health behaviors. Individual differences (such as consideration of future consequences) may potentiate the effects of behavioral willingness on health-risk outcomes, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Consideration of future consequence refers to the extent to which the individual considers the potential future outcomes of the current behavior and the extent to which the individual is affected by those potential future outcomes (Cao and Xia, 2020). Consideration of future consequence can effectively predict a lot of individual behaviors (Lewis et al, 2018), such as following rules and regulations, self-control, reducing alcohol abuse, etc. Safety performance can largely be considered as a future variable due to the lag between safety behavior and safety consequence.…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of future consequence refers to the extent to which the individual considers the potential future outcomes of the current behavior and the extent to which the individual is affected by those potential future outcomes (Cao and Xia, 2020). Consideration of future consequence can effectively predict a lot of individual behaviors (Lewis et al, 2018), such as following rules and regulations, self-control, reducing alcohol abuse, etc. Safety performance can largely be considered as a future variable due to the lag between safety behavior and safety consequence.…”
Section: Introductionmentioning
confidence: 99%
“…Purposive sampling was employed to ensure the student researchers and participants were embedded in the same culture. Social network recruitment strategies facilitate open and frank responses ( Lewis et al, 2018 ) and have been effectively employed in previous research on health and sensitive research areas ( Akhtar et al, 2020 , Brown et al, 2013 ). Participation took approximately 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Cannabis prototypes were measured using three open-ended questions that asked students to write a list of words to describe how their peers would perceive a student of the same gender as themselves based on the hypothetical student’s cannabis use (never uses, sometimes uses, is a heavy user) (adapted from Lewis et al; 22 Robertson & Tustin 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Prototype research has informed research on alcohol 21 and is an emerging area of research in the context of cannabis. For example, Lewis et al 22 found that individuals’ favorable perceptions of a typical cannabis user were associated with increased willingness to use cannabis themselves.…”
Section: Introductionmentioning
confidence: 99%